Face mask use and disposal behaviour of frontline young doctors during the COVID-19 pandemic: a two-year study - Shibaji Gupta; Arup Chakraborty; Rudradeep Banerjee; Abhishek De; Sohini Halder; Debasis Das (Journal of Infection in Developing Countries)
Introduction: The COVID-19 pandemic has severely affected India in spite of an ongoing vaccination campaign. The doctors are at greater risk of COVID-19 and face masks are a protective measure against this threat. We assessed the use and disposal of face masks among postgraduate trainees (PGTs) working on the COVID-19 frontline in an Indian medical college.